An proposal for the improvement of social interest housing projects from the perspective of its end users - MÃnica Veras Morais (2015)
In Brazil, the last decades have seen the introduction of the private sector in housing provision policies. In this scenario, the government reduced its participation in the process, focusing solely on the roles as a articulator and performing regulatory tasks , through lending to constr uction and obtainment of housing ; context into which the My House My Life program (PMCMV) resides. Simultaneously, post - occupancy evaluation's researches (POE) have gained more prominence in the diagnostics concerning housing production in the country, contributing with essential information to feedback into the design p rocess and to encourage improvements in the quality of the environment built, generating greater value to customers. In this sense, both the POE studies and the specific evaluation studies concerning the measurement of satisfaction levels find validation i n theories and methodologies that have arisen from Psychology, e.g. Environmental Psychology and Social Representations. From this context, the research that is referred to in this document aims to propose improvements to social - interest housing projects ( HIS), from the perspective of the end user. Therefore, by means of adopting a multiple case study as a research strategy, projects delivered from PMCMV (track 1) in CearÃ, were seized as the object and the residents that received the benefits were seized a s the subject. Using multiple data collection instruments, individual interviews and focus groups amongst them, comments of a positive, neutral and negative nature were captured concerning various aspects of housing, as divulged by the participating reside nts during the application of the instruments of data collection. After organizing the collected data into tables, the respondents' points of satisfaction and dissatisfaction concerning the pro duct received were identified; f urthermore, through the applic ation of tools designed for this very purpose, the relevance bestowed by the participants to various aspects of housing were measured. Subsequently, the dissatisfactions detected were turned into improvement guidelines for future development of HIS, consid ering, thusly, the perspective of end users. Finally, contributions to proposals that aim to improve the quality of housing developments were made, through the use of tools derived from the person - environment studies